Effects of cavity depth (moderate vs. deep with pulp exposure) on the release of prostaglandin E2 and nitric oxide in rat mandibular incisors - Riyadh, Hassanien; Mahdee, Anas F. (Frontiers in Dental Medicine, 2025)
Background/objectivesInflammatory mediators such as prostaglandin E2 (PGE2) and nitric oxide (NO) are key indicators of pulp response to mechanical trauma. However, the influence of cavity depth on their release dynamics remains unclear. This study aimed to evaluate the effects of different cavity depths—moderate (without pulp exposure) and deep (with pulp exposure)—on the release of PGE2 and NO in the pulp tissue of rat mandibular incisors at two time intervals (3 and 9 h).MethodsIn total, 40 male Wistar rats were divided into two main groups (n = 20) based on cavity depth. A split-mouth design was used, with cavities of different depths prepared on the left mandibular incisors, leaving the right incisors without cavities as controls. All the prepared cavities were sealed with glass ionomer filling until 3 or 9 h (n = 10), when pulp tissue was removed. Homogenates were prepared and analyzed by ELISA for PGE2 and NO levels.ResultsCavities without pulp exposure elicited 2.1-fold higher PGE2 (median: 3.44 vs. 1.81 ng/mL; p < 0.001) and 1.3-fold higher NO (median: 55.45 vs. 43.76 μmol/L; p < 0.01) compared to exposed cavities at 3 h—a paradoxical finding suggesting intact pulp architecture potentiates acute inflammatory signaling. This disparity persisted at 9 h (PGE2: 3.18 vs. 1.81 ng/mL; NO: 49.94 vs. 44.98 μmol/L), though with attenuated significance (p < 0.05).ConclusionCavity preparation induces an early inflammatory response in the pulp, as indicated by increased PGE2 and NO levels. The inflammatory response was more pronounced in cavities without pulp exposure, suggesting that maintaining pulp integrity favors a regulated inflammatory response conducive to healing, while exposure may promote irreversible damage.